MODEL PEMBELAJARAN TERPADU DENGAN PENDEKATAN FUNGSIONAL PADA MATA KULIAH HISTOLOGI - Ambardini, Rachmah Laksmi (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2009)
The aim of this study was to find out whether the integrated learning model through the functional approach could improve the students’ academic achievement in the Histology subject. This action research was done in three cycles during the second semester of the 2007/2008 academic year. Each cycle consisted of four activities: planning, implementation, observation, and reflection. The participants of the study were PJKR students of B Group of the Histology class. The research instruments were field notes, practicum worksheets, and tests. Data were analyzed descriptively. Results of the study indicated that: (1) the integrated learning model through the functional approach improved the students’ academic achievement in the Histology class; and (2) the most effective learning strategies in the Histology class were conducted in three steps: (a) explanation of the three dimension structure before the two dimension structure, (b) laboratory practice focused on identification of Histology specimen through active learning , (c) small group discussion with subject matter informed one week before the class.